Tidbits for the synthesis of bis(2‐sulfanylethyl)amido (SEA) polystyrene resin, SEA peptides and peptide thioesters‡. (19th November 2013) - Ollivier, Nathalie; Raibaut, Laurent; Blanpain, Annick; Desmet, Rémi; Dheur, Julien; Mhidia, Reda; Boll, Emmanuelle; Drobecq, Hervé; Pira, Silvain L.; Melnyk, Oleg; Becker, Christian
<x xml:space="preserve">Abstract</x> Protein total chemical synthesis enables the atom‐by‐atom control of the protein structure and therefore has a great potential for studying protein function. Native chemical ligation of C‐terminal peptide thioesters with N‐terminal cysteinyl peptides and related methodologies are central to the field of protein total synthesis. Consequently, methods enabling the facile synthesis of peptide thioesters using Fmoc‐SPPS are of great value. Herein, we provide a detailed protocol for the preparation of bis(2‐sulfanylethyl)amino polystyrene resin as a starting point for the synthesis of C‐terminal bis(2‐sulfanylethyl)amido peptides and of peptide thioesters derived from 3‐mercaptopropionic acid. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd.